Transport of Axl2p Depends on Erv14p, an ER–Vesicle Protein Related to the Drosophila cornichon Gene Product - Powers, Jacqueline (The Rockefeller University Press, 1998)
COPII-coated ER-derived transport vesicles from Saccharomyces cerevisiae contain a distinct set of membrane-bound polypeptides. One of these polypeptides, termed Erv14p (ER–vesicle protein of 14 kD), corresponds to an open reading frame on yeast chromosome VII that is predicted to encode an integral membrane protein and shares sequence identity with the Drosophila cornichon gene product. Experiments with an epitope-tagged version of Erv14p indicate that this protein localizes to the ER and is selectively packaged into COPII-coated vesicles. Haploid cells that lack Erv14p are viable but display a modest defect in bud site selection because a transmembrane secretory protein, Axl2p, is not efficiently delivered to the cell surface. Axl2p is required for selection of axial growth sites and normally localizes to nascent bud tips or the mother bud neck. In erv14Δ strains, Axl2p accumulates in the ER while other secretory proteins are transported at wild-type rates. We propose that Erv14p is required for the export of specific secretory cargo from the ER. The polarity defect of erv14Δ yeast cells is reminiscent of cornichon mutants, in which egg chambers fail to establish proper asymmetry during early stages of oogenesis. These results suggest an unforeseen conservation in mechanisms producing cell polarity shared between yeast and Drosophila.